Strontium Isotopes Support Small Home Ranges for Extinct Lemurs - Crowley, Brooke Erin; Godfrey, Laurie Rohde (Frontiers in Ecology and Evolution, 2019)
Among mammals, including anthropoid primates, the primary factors that affect mobility are body size (larger-bodied species move more than smaller ones), diet (frugivores and trophic omnivores are more mobile than folivores), and habit (terrestrial taxa have larger home ranges than arboreal ones). If similar factors hold for Lemuriformes, we would expect large-bodied (particularly frugivorous) extinct lemurs to have been more mobile than smaller-bodied (particularly folivorous) extant species. Yet multiple lines of evidence (e.g., low Retzius Periodicities, small semicircular canal size, small relative brain size) suggest that extinct lemurs were relatively inactive. If so, they may have had relatively small home ranges, perhaps on par with smaller-bodied extant lemurs. We used strontium isotopes (87Sr/86Sr), which vary spatially primarily as a function of geology, to compare mobility for eight lemur genera: Eulemur, Lemur, Lepilemur and Propithecus (extant), and Archaeolemur, Megaladapis, Pachylemur and Palaeopropithecus (extinct). Subfossils came from two sites: Ankilitelo/Mikoboka, a series of sinkholes in a limestone plateau, and Ampasambazimba, a wetland underlain by a variety of igneous and metamorphic rocks. Within either site, we expected more mobile taxa to exhibit more variable 87Sr/86Sr, reflecting larger movement across a diversity of geologies. We found no differences in median 87Sr/86Sr or variance between extinct and extant lemurs at either site (Wilcoxon and Bartlett p>0.05 for all comparisons). There were apparent but insignificant differences among genera (Kruskal-Wallis and Bartlett p>0.05). Isotopic variability was greater at Ampasambazimba than at Ankilitelo/Mikoboka, reflecting differences in the underlying geology. One Palaeopropithecus from Ankilitelo/Mikoboka and one Eulemur from Ampasambazimba had unusually elevated 87Sr/86Sr. We suspect that both of these individuals were deposited at their respective sites by a predatory bird. These results demonstrate the value of 87Sr/86Sr for testing hypotheses related to the behavior of now-extinct species. Strontium isotopes support low mobility for extinct lemurs, and suggest that Lemuriformes as a whole differ from anthropoids in having relatively depressed basal metabolism and reduced activity levels. These traits reduce energetic expenditure, and likely developed in response to Madagascar’s harsh environments. However, small home ranges also make lemurs more vulnerable to extinction.